Scholarly Research Projects Benefit Medical Students' Research Productivity and Residency Choice: Outcomes From the University of Pittsburgh School of Medicine. (November 2018) - Conroy, Molly B.; Shaffiey, Shahab; Jones, Sarah; Hackam, David J.; Sowa, Gwendolyn; Winger, Daniel G.; Wang, Li; Boninger, Michael L.; Wagner, Amy K.; Levine, Arthur S.
Abstract : Purpose: Many medical schools require scholarly research projects. However, outcomes data from these initiatives are scarce. The authors studied the impact of the Scholarly Research Project (SRP), a four-year longitudinal requirement for all students at the University of Pittsburgh School of Medicine (UPSOM), on research productivity and residency match. Method: The authors conducted a longitudinal study of non-dual-degree UPSOM graduates in 2006 (n = 121, non-SRP participants) versus 2008 (n = 118), 2010 (n = 106), and 2012 (n = 132), all SRP participants. The authors used PubMed for publication data, National Resident Matching Program for residency match results, and Blue Ridge Institute for Medical Research for National Institutes of Health funding rank for residency-affiliated academic institutions. Results: Research productivity of students increased for those completing the SRP, measured as a greater proportion of students with publications (27.3% in 2006 vs. 45.8% in 2008, 55.7% in 2010, and 54.5% in 2012; P < .001) and first-authorship (9.9% in 2006 vs. 26.3% in 2008, 33.0% in 2010, and 35.6% in 2012; P < .001). Across years, there was a significantly greater proportion of students with peer-reviewed publications matched in higher-ranked residency programs (57.0% with publications in the top 10%, 52.7% in the top 10%–25%, 32.4% in the top 25%–50%, 41.2% in the bottom 50%, and 45.2% in unranked programs; P = .018). Conclusions: Longitudinal research experiences for medical students may be one effective tool in fostering student publications and interest in extending training in a research-focused medical center. Abstract : Supplemental Digital Content is available in the text.